2016
DOI: 10.23917/jep.v17i1.1633
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Model of Falcataria-Based Farm Forestry: A Duration Analysis Approach

Abstract: Farm forestry is a form of farming systems that provides economic and environmental benefits. The salient feature of this system is the incorporation of commercial perennial plants, in particular forest trees, into farming systems and can take many forms, including timber belts, alleys and widespread tree plantings. While the system in some locations has been well adopted, the farmers or land users in other location are reluctant to adopt them, although the traits of farmers and farm land in both locations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…The value of the incremental B/C ratio is expected to encourage farmers to apply biopore dual function of biopore technology with green manure media. Irawan (2016) research support this analysis. The results showed that farmers with a high dependence on farming yield tend to adopt soil conservation technology more quickly than farmers who have income variations outside of farming.…”
Section: Incremental B/c Ratiosupporting
confidence: 72%
“…The value of the incremental B/C ratio is expected to encourage farmers to apply biopore dual function of biopore technology with green manure media. Irawan (2016) research support this analysis. The results showed that farmers with a high dependence on farming yield tend to adopt soil conservation technology more quickly than farmers who have income variations outside of farming.…”
Section: Incremental B/c Ratiosupporting
confidence: 72%
“…Agriculture is highly dependent on natural conditions, and good terrain can provide convenience for technology and reduce costs. Usually, flat terrain and concentrated distribution are favorable for members to adopt GCT [11].…”
Section: External Driving Role Of Educationmentioning
confidence: 99%
“…There are abundant research on farmers' GCT adoption in academic circles. It is generally believed that GCT adoption is related to farmers' age [6], education level [7], geographical environment [8], farm size [9], income [10], labor force [11], etc. Moreover, GCT adoption is also related to external factors such as government regulation [12], technology integration and application [13], technical training [14], market supervision, and docking [15].…”
Section: Introductionmentioning
confidence: 99%
“…Economic development can be done by increasing community per capita [9] or increasing living standards by increasing community real income [10]. Indicators include (1) Real National Income,, (2) Real income per capita, (3) labor and unemployment, (4) public welfare, an increase in material welfare in the community can be seen from the distribution of goods and services, the smooth distribution of goods and services illustrates the distribution of income per capita in society [10].…”
Section: Increasing Income Of Communitymentioning
confidence: 99%